Enhancing elementary students’ numeracy skills through a Ngadhu Bhaga ethnomathematics-based learning approach - Wewe, Melkior; Bela, Maria Editha; Wangge, Maria CT; Bhoke, Wilibaldus (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Numeracy is an essential skill that enables students to interpret and apply numerical information in everyday life. However, mathematics learning often lacks connections to students’ cultural contexts, limiting the development of numeracy skills. Aims: This study aims to examine the effectiveness of the Ngadhu Bhaga ethnomathematics-based learning approach in enhancing elementary students’ numeracy skills and to explore students’ learning experiences, teachers’ perceptions, and teacher–student interactions during its implementation. Method: This study employed a mixed-methods design with a post-test control group experiment. The participants were 40 fifth-grade students from Regina Pacis Bajawa Elementary School, Indonesia. Quantitative data were collected using numeracy tests, while qualitative data were obtained through questionnaires, interviews, and classroom observations. Results: The findings show that students who learned through the Ngadhu Bhaga ethnomathematics-based approach achieved higher numeracy scores than those who learned through conventional instruction. The approach also promoted active participation, strengthened teacher–student interaction, and increased students’ engagement in mathematics learning. Conclusion: Integrating local cultural contexts through the Ngadhu Bhaga ethnomathematics approach can effectively support the development of elementary students’ numeracy skills and create a more meaningful learning environment